TATA LAKSANAâBEHAVIORAL ACTIVATIONâ UNTUK MENURUNKAN TINGKAT DEPRESI PADA PASIEN STROKE - , IMA SANTIKA JAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The data in 2012 showed that Indonesia was the country with the largest number of stroke patients in Asia. This is very alarming because stroke patients usually feel inferior and uncontrolled emotions so they are susceptible to depression. Depression in patients of stroke causes a decrease in health, quality of life, and positive feelings. Behavioral Activation (BA) is a technique that consists of various series of activities that can increase happiness, productivity, and patient's meaning of life. BA for depression in stroke patients still needs to be developed more in clinical setting. Therefore, we need a treatment guideline for psychologists in conducting assessment, diagnosis, and treatment for depression in stroke patients based on BA principles. This study aims to verify the effectiveness of BA guideline by evaluating psychologistâs self efficacy in delivering service for stroke patients, patientsâ satisfaction of service, & patientsâ BDI scores. Data were analyzed by visual inspection and qualitative analysis. Keywords : treatment guideline, behavior activation, stroke, depression